Developing Academic Listening Skills in English Language Learning at Higher Education - Deasyy Yunita Siregar; Aura Azzahra; Meisya Khani Lubis; Nabila Azzara; Rizki Nurhasanah Lubis (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Academic listening is a crucial skill for university students, particularly in English as a Foreign Language (EFL) contexts where English is widely used for academic purposes. This skill enables students to understand lectures, follow academic discussions, take effective notes, and process spoken information critically. However, many EFL students still experience difficulties in academic listening due to limited exposure to authentic academic input, lack of listening strategies, and linguistic challenges. This conceptual article discusses the concept of academic listening, its characteristics in higher education, common challenges faced by EFL students, and pedagogical strategies for developing academic listening skills. Drawing on relevant theories and findings from previous studies, this article emphasizes the importance of strategy-based instruction, the use of authentic academic materials, and the active role of lecturers in supporting students’ academic listening development. The discussion is presented using clear and accessible academic language to support English language teaching practices at the university level.